Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Keywords: international political economy; international relations

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Keywords: BLOCK, Fred L.; SOMERS, Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.